HarpCI, Empowering Performers to Control and Transform Harp Sounds in Live Performance. - Di Donato, Balandino; Dooley, James; Coccioli, Lamberto (Contemporary Music Review, 2019)
The goal of our research is to provide harpists with the tools to control and transform the sounds of their instrument in a natural and musical way. We consider the development of music with live electronics, with particular reference to the harp repertoire, and include interviews with six harpists that use technology in their professional performance practice. We then present HarpCI, a case study that explores how gestures can be used to control and transform sound and light projection in live performance with the electric harp. HarpCI draws on research from the areas Human Computer Interaction (HCI) and Music Interaction Design (MiXD) to extend the creative possibilities available to the performer, and demonstrates our approach to bridging the gap between the performer/composer and the harp on one side, and the technology on the other. We discuss the use of guitar pedals with the electric harp, and the limitations they impose, and then introduce the MyoSpat system as a potential solution to this issue. MyoSpat aims to give musicians control over auditory and visual aspects of the performance through easy to learn, intuitive and natural hand gestures. It also aims to enhance the compositional process for instrument and live electronics, through a new way of music notation for gesturally controlled interactive systems. The system uses the Myo armband gestural controller, a device to control live sound processing that is non-invasive to instrumental technique and performer. The combination of these elements allows the performer to experience a tangible connection between gesture and sound production. Finally, we describe the experience of Eleanor Turner, who composed and performed The Wood and the Water (Turner 2016) using MyoSpat, and we conclude by presenting the outcomes from HarpCI workshops delivered at Cardiff Metropolitan University for Camac Harp Weekend, Royal Birmingham Conservatoire's Integra Lab and Southampton University.